Emergence and diversification of dengue 2 cosmopolitan genotype in Pakistan, 2011. - Mohammad A Khan (Public Library of Science (PLoS), 2013)
Major dengue epidemics have been observed in the Indian subcontinent since the 1980s and have occurred with increased hospitalizations and mortality. In 2011, the first major epidemic of dengue occurred in Lahore, the second largest city in Pakistan, and resulted in 21,685 confirmed cases and 350 deaths. To investigate the possible viral causes for the increased epidemic activity, we determined the predominant serotype and characterized the viruses genetically. Of 50 patients carefully selected as probable dengue fever or dengue hemorrhagic fever, 34 were positive by virologic testing (i.e. PCR and/or virus isolation). DENV-2 was detected in 32 patients and DENV-1 in two. A total of 24 partial and three full DENV genomes were sequenced. Phylogenetic analyses of the capsid (C), pre-membrane (prM), and envelope genes comprising 2500 nucleotides in length indicated that all DENV-2 isolates in Pakistan since 2007 form a monophyletic lineage that is endemic in the country. These viruses were all of the cosmopolitan genotype (IV) and most closely related to viruses isolated in India and Sri Lanka in the past two decades. Phylogenetic analyses of data currently available in GenBank suggest that the Cosmopolitan genotype has diverged into two geographically distinct sub-lineages: sub-lineage IV-a has only been observed in Southeast Asia, China and Oceania, while IV-b is prevalent in the Indian subcontinent. These results highlight the increased diversity of dengue viruses as they spread geographically within the region.